2018
DOI: 10.1016/j.molmet.2018.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin transport across the blood–brain barrier can occur independently of the growth hormone secretagogue receptor

Abstract: ObjectiveThe blood–brain barrier (BBB) regulates the entry of substrates and peptides into the brain. Ghrelin is mainly produced in the stomach but exerts its actions in the central nervous system (CNS) by crossing the BBB. Once present in the CNS, ghrelin can act in the hypothalamus to regulate food intake, in the hippocampus to regulate neurogenesis, and in the olfactory bulb to regulate food-seeking behavior. The goal of this study was to determine whether the primary signaling receptor for ghrelin, the gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 52 publications
2
49
0
1
Order By: Relevance
“…On one hand, although only acyl ghrelin is able to activate GHSR, 66–94% of circulating ghrelin is actually found in the des-acyl form [55], [56], [57], due to the activity of esterases and APT-1 [49]. In addition, ghrelin has a limited capacity to cross the blood-brain-barrier [58]. On the other hand, Dln101 emerges as a relevant candidate to maintain GHSR activation due to its increased stability in the acylated residue.…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, although only acyl ghrelin is able to activate GHSR, 66–94% of circulating ghrelin is actually found in the des-acyl form [55], [56], [57], due to the activity of esterases and APT-1 [49]. In addition, ghrelin has a limited capacity to cross the blood-brain-barrier [58]. On the other hand, Dln101 emerges as a relevant candidate to maintain GHSR activation due to its increased stability in the acylated residue.…”
Section: Discussionmentioning
confidence: 99%
“…A further study showed that the highest uptake of systemically injected 131 I‐ghrelin occurs in the occipital cortex, olfactory bulb and hypothalamus, in that order, and that ghrelin uptake in the hippocampus is similar to the uptake in the whole brain . Further studies showed that the transport of human 131 I‐ghrelin into the brain is affected by the physiological status, being decreased in obese mice and promoted by hypertriglyceridaemia, independent of the presence of GHSR . Another study showed that 131 I‐ghrelin interacts with RBE4 cerebral microvessel endothelial cells .…”
Section: Potential Mechanisms Transporting Plasma Ghrelin Into the Brainmentioning
confidence: 93%
“…These findings suggest that, similar to other islet and gastrointestinal hormones, acyl ghrelin may act centrally to regulate insulin levels and glucose metabolism. This is supported by observations that a small amount of acyl and DAG can cross the blood‐brain barrier to reach the central nervous system …”
Section: Ghrelin Regulation Of Insulin Secretion: the Role Of The Cenmentioning
confidence: 66%